2015
DOI: 10.1007/s40993-015-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Weierstrass mock modular forms and elliptic curves

Abstract: Mock modular forms, which give the theoretical framework for Ramanujan's enigmatic mock theta functions, play many roles in mathematics. We study their role in the context of modular parameterizations of elliptic curves E/Q. We show that mock modular forms which arise from Weierstrass ζ -functions encode the central L-values and L-derivatives which occur in the Birch and Swinnerton-Dyer Conjecture. By defining a theta lift using a kernel recently studied by Hövel, we obtain canonical weight 1/2 harmonic Maass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(85 citation statements)
references
References 54 publications
(74 reference statements)
2
83
0
Order By: Relevance
“…Further, in [13], Ono and the first author used a variant of the Kudla-Millson theta lift to find a finite algebraic formula for the partition function p(n) in terms of traces of CM-values of a certain non-holomorphic modular function. Recently, a similar theta lift was used in [4] to prove a refinement of a theorem of [12] connecting the vanishing of the central derivative of the twisted L-function of an even weight newform and the rationality of some coefficient of the holomorphic part of a half-integral weight harmonic Maass form. This so-called Millson theta lift, which maps weight 0 to weight 1/2 harmonic Maass forms, was studied in great detail by Alfes-Neumann in her thesis [3], and by AlfesNeumann and the second author in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Further, in [13], Ono and the first author used a variant of the Kudla-Millson theta lift to find a finite algebraic formula for the partition function p(n) in terms of traces of CM-values of a certain non-holomorphic modular function. Recently, a similar theta lift was used in [4] to prove a refinement of a theorem of [12] connecting the vanishing of the central derivative of the twisted L-function of an even weight newform and the rationality of some coefficient of the holomorphic part of a half-integral weight harmonic Maass form. This so-called Millson theta lift, which maps weight 0 to weight 1/2 harmonic Maass forms, was studied in great detail by Alfes-Neumann in her thesis [3], and by AlfesNeumann and the second author in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that the Moonshine phenomenon we prove in this paper is not directly related to this generalized moonshine considered by Queen, but more reminiscent of the following. In 2011, Eguchi et al [19] observed connections like the ones between the dimensions of irreducible representations of the Monster group and coefficients of the modular function J for the largest Mathieu group M 24 and a certain weight 1 2 mock theta function. Cheng et al [12,13] generalized this to Moonshine for groups associated with the 23 Niemeier lattices, the non-isometric even unimodular root lattices in dimension 24, which has become known as the Umbral Moonshine Conjecture.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Definition 2.1 A vector space V is called a superspace, if it is equipped with a Z/2Z-grading V = V (0) ⊕ V (1) , where V (0) is called the even and V (1) is called the odd part of V . For an endomorphism α of V respecting this grading, i.e., α(V (i) ) ⊆ V (i) , we define its supertrace to be strace(α) = trace α| V (0) − trace α| V (1) . Now let G be a finite group and (V, ρ) a representation of G. If the G-module V admits a decomposition into an even and odd part as above which is compatible with the G-action, we call V a G-supermodule.…”
Section: Supermodulesmentioning
confidence: 99%
See 2 more Smart Citations